Bridge evaluation through nondestructive testing in comparison with visual inspection - Adnan, Azlan; Alih, Sophia C.; Mirasa, Karim (2006)
This paper presents a nondestructive testing method in evaluating bridge condition in comparison with visual inspection that has been used for ages. While condition ratings are all qualitative and defined primarily as sets of visual indicators in routine inspection, nondestructive testing are more quantitative and has large potential in determining damages inside the structure that are not visible. Hence, an attempt to integrate the nondestructive evaluation and bridge management system has been carried out by several researchers. This study is aimed to determine bridge strength through nondestructive testing and thus establish correlation between visual inspection rating and the nondestructive testing results. 75 concrete bridges under the supervision of Public Works Department (Malaysia) have been selected for the preliminary testing which includes the Rebound Hammer test, Ultrasonic Pulse Velocity, and electromagnetic cover meter. However, this paper will only discuss the methodology and results from Rebound hammer test. Generally, this study indicates good correlation between visual rating and strength from Rebound Hammer result. Ratings assigned to the bridge during visual inspection are within an acceptable range in reflecting the bridge strength. Rebound hammer has a potential to be a preliminary test in evaluating the bridge condition. However, since the nondestructive testing is not always readily available and there may be problems occurred with the lack of experienced inspectors to conduct the test, the implementation of this method in routine inspection may be limited. Therefore, an initial study to develop an intelligent rating system combining both nondestructive test data and visual inspection rating has been conducted in the later stage of this research as part of the solution to this problem.